(untitled) (Journal of Special Education and Rehabilitation, 2014)
The Fourth International Conference with the main topic “Modern Aspects of Special Education and Rehabilitation of Persons with Disabilities” was held from 17th to 19th October, in the hotel “Metropol” in Ohrid. The conference was organized by the Institute of Special Education and Rehabilitation, Faculty of Philosophy in Skopje, which celebrated its anniversary “20 Years Studies of Special Education and Rehabilitation”. The conference was attended by 135 participants, including notable names in the field of special education and rehabilitation, prominent researchers, practitioners, special educators and professional associates from the country and abroad, as well as a significant number of students and postgraduates. The conference was opened on 17th October by the Head of the Institute of Special Education and Rehabilitation, prof. Zora Jachova PhD, and the President of the Organizational board, doc. Zoran Kitkanj Phd. The Dean of the Faculty of Philosophy in Skopje, prof. Goran Ajdisnki Phd and a representative from the Ministry of Education and Science of the Republic of Macedonia, Head of the Department of Higher Education, Mr. Borche Aleksov welcomed the attendees. After the opening speeches, the orchestra from the State school for rehabilitation of children and youth with visual impairment “Dimitar Vlahov” had a performance. After that there were plenary lectures. The plenary lectures were held by the following lecturers: • Prof. Ljupcho Ajdinski PhD, talked about “The development and state of the system for rehabilitation of persons with disabilities in the Republic of Macedonia”; • Doc. Zoran Kitkanj PhD talked about “Juvenile delinquency problem in modern society - state, response and challenges”; • Luk Zelderloo, general secretary of EASPD, through an internet live stream, presented the EASPD perspective on “Inclusive Learning: Challenges and Possibilities”; • Dr. Davis Preece talked about “The effect of implementing training for positive behavioral support for parents of children with autism and related behaviors problems” and • Prof. Risto Petrov PhD presented “The treatment of people with intellectual disability and health consequences for employers”. After the plenary lectures, plaques and certificates of appreciation from the Institute of Special Education and Rehabilitation for outstanding contribution in the formation and development of the studies of special education were awarded. They were awarded by the Head of the Institute of Special Education and Rehabilitation, prof. Zora Jachova PhD. Awards and certificates were also awarded by the Foundation “Prof. Ljupcho Ajdinski” and they were delivered by prof. Ljupcho Ajdisnki PhD. Of the total reported 115 papers, 67 were presented at the conference, divided into four categories: rehabilitation, education, quality of life and behavioral disorders. Besides representatives of the country, guests from Serbia, Montenegro, Croatia, England and the United States of America actively participated in the sessions and discussions. The presented papers will be published in the Book of papers after the conference. The rich and various program enabled participants to broaden their professional knowledge and experience. AAfter the two workshops: “How autonomic dysfunction leads to cognitive problems and influences learning” by Graham Ewing and “Systematical family approach in work with families of child with disabilities” by Prof. Marija Raleva PhD and Liljana Trpchevska, the conference was closed by the President of the Scientific board Prof. Natasha Chichevska-Jovanova PhD. After the closing ceremony all the participants enjoyed in the touristic sightseeing of Ohrid. The abstracts of papers and a gallery of photos from the conference can be found on the official website: http://maser.fzf.ukim.edu.mk.